Weight-adjusted waist index and cardiovascular disease: a population-based study in Ravansar, Iran - Sepehr Sadafi; Ali Azizi; Ebrahim Shakiba; Yahya Pasdar (Archives of Public Health)
Abstract Background The weight-adjusted-waist index (WWI) is a relatively new index to obesity. This study aimed to explore the reationship between WWI and cardiovascular disease (CVD). Methods This cross-sectional study included 8,899 participants aged 35 to 65 from the Ravansar non-communicable diseases (RaNCD) cohort study in Ravansar, Iran. The WWI was calculated by dividing waist circumference (WC) by the square root of weight. The receiver operating characteristic (ROC) curve was utilized to assess the predictive performance of WWI in relation to CVD. The study applied multiple logistic regression to assess the association between WWI and CVD. Results Participants had an average age of 47.52 ± 8.29 years, with 45.30% being men and 41.13% residing in rural areas. The prevalence of CVD was found to be 17.36%. A positive correlation between WWI and CVD was obseved, with individuals in the highest WWI quartile having a 36% (OR = 1.36, 95%CI: 1.11, 1.78) greater odds of CVD compared to those in the lowest quartile (OR = 1.03, 95%CI: 0.79, 1.33) (ptrend = 0.010). Subgroup analyses indicated stronger links between WWI and CVD among participants over 50, males, urban residents, those of high socioeconomic status (SES), and passive smokers (p < 0.001). The ROC analysis revealed that WWI is a greater ability in predicting CVD (AUC: 0.64, 95%CI: 0.61, 0.64) compared to body mass index (BMI) (AUC: 0.60, 95%CI: 0.58, 0.61) and WC (AUC: 0.61, 95%CI: 0.59, 0.62). Conclusion The increase in WWI elevates the odds of CVD, making the management of WWI crucial for CVD prevention.